2002
DOI: 10.1038/sj.bmt.1703647
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a hybrid central venous catheter utilized for both peripheral blood stem cell harvest and transplant support of patients undergoing autologous peripheral blood stem cell transplantation

Abstract: Summary:Patients undergoing autologous peripheral blood stem cell transplantation (PBSC) frequently require the sequential insertion of two central venous catheters, one for leukapheresis and one for transplant support. Hybrid catheters suitable for leukapheresis and longterm use have been increasingly used, but there is limited information regarding their performance and complication rate. The purpose of this study was to determine the performance of the Pheres-Flow hybrid catheter when utilized for both leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In addition, a high proportion of centers utilized the double-lumen plasmapheresis/hemodialysis long-term catheter, of the Hickmann or Quinton type, for autologous transplantation, and most of the centers utilized different catheters for PBSC harvest and post transplant support. This is of interest because previous studies demonstrate a relatively high complication rate for longterm hemodialysis central venous catheters with only one third of catheters being useful throughout the entire treatment period in contrast to more recent reports utilizing hybrid central venous catheters for PBSC harvest and post transplant support [5,12]. Also of interest is the fact that our survey demonstrated that the subclavian vein is the preferred VAD insertion site (62%) in contrast to the internal jugular vein (31%) despite the easier access and lower complication rate of the internal jugular vein access [8].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a high proportion of centers utilized the double-lumen plasmapheresis/hemodialysis long-term catheter, of the Hickmann or Quinton type, for autologous transplantation, and most of the centers utilized different catheters for PBSC harvest and post transplant support. This is of interest because previous studies demonstrate a relatively high complication rate for longterm hemodialysis central venous catheters with only one third of catheters being useful throughout the entire treatment period in contrast to more recent reports utilizing hybrid central venous catheters for PBSC harvest and post transplant support [5,12]. Also of interest is the fact that our survey demonstrated that the subclavian vein is the preferred VAD insertion site (62%) in contrast to the internal jugular vein (31%) despite the easier access and lower complication rate of the internal jugular vein access [8].…”
Section: Discussionmentioning
confidence: 98%
“…There are some studies, mostly performed in children, studying complications of a single catheter used for both stem-cell apheresis and high-dose chemotherapy, but comparative studies are not available. [18][19][20][21][22][23] Most of these studies indicate that use of a single catheter is safe and effective, but sometimes as few as 31% of patients are able to complete the whole procedure with only one catheter. 18 In our study the catheter for dual purpose had to be removed before the end of the procedure because of infectious complications in 37.1% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, frequent mechanical and infectious complications have been reported (3.6-8.92% infections and 1.8-3.5% occlusions), as well as some cases of pneumothorax at the time of catheter insertion. 14,15 Dual-or multi-lumen tunneled catheters may also be used for both apheresis and grafting, 1,3,[16][17][18] with a flow rate of approximately 40 ml/min (range 25-65 ml/min). A study by Restrepo et al 18 using Pheres Flow triple-lumen tunneled silicone catheters in adults has reported 29% occlusions and 22% infectious complications.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Dual-or multi-lumen tunneled catheters may also be used for both apheresis and grafting, 1,3,[16][17][18] with a flow rate of approximately 40 ml/min (range 25-65 ml/min). A study by Restrepo et al 18 using Pheres Flow triple-lumen tunneled silicone catheters in adults has reported 29% occlusions and 22% infectious complications. Gorlin et al 1 have demonstrated that using large size catheters in children can increase the risk of complications at insertion (2 pneumothorax in 14 patients) and the incidence of thrombosis (6 cases in total, 3 necessitating removal of the device).…”
Section: Discussionmentioning
confidence: 99%